2020
DOI: 10.1590/1983-40632020v5059377
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea development under different temperatures and carbon dioxide concentrations

Abstract: ABSTRACT The increase of CO2 concentrations and temperatures may affect the plant development and production. This study aimed to evaluate the impact of the increased temperature and carbon dioxide concentration on the development of cowpea cultivars. The experiment was conducted in growth chambers, with control of CO2 and temperature. A completely randomized design was carried out, in a 4 x 3 x 2 factorial arrangement [cultivar x temperature (day/night) x CO2], with three replicates. The duration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…[57], but also cowpea (Vigna unguiculata [L.] Walp.) [58,59] and grass species [60]. The considerable variation in crop responses to future climate was described for chickpea in previous studies for South Asia and East Africa [61].…”
Section: Discussionmentioning
confidence: 85%
“…[57], but also cowpea (Vigna unguiculata [L.] Walp.) [58,59] and grass species [60]. The considerable variation in crop responses to future climate was described for chickpea in previous studies for South Asia and East Africa [61].…”
Section: Discussionmentioning
confidence: 85%
“…Decreases in evapotranspiration and in the duration of the crop cycle for rainfed cowpea are also expected in different warming scenarios (Cavalcante Junior et al 2016). Angelotti et al (2020) found in a controlled growth chamber that some cowpea cultivars show higher dry matter production and number/weight of seeds under elevated CO 2 concentration (500 ppm). Besides yield increase of the plants, elevated CO 2 concentration improves plant water relations by reducing its stomatal conductance (Hatfield and Dold 2019) as observed for rice (Kumar et al 2019) and mung bean (Gao et al 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Semi-arid regions are the more vulnerable to climate change and extreme temperature events (Djanaguiraman et al, 2018). The Brazilian semi-arid region has an average temperature of approximately 26 °C (Angelotti et al, 2020) and according to the data described by the Rules for Seed Analysis (Regras para Análise de Sementes -RAS) the ideal temperature for the germination of the cowpea is 25 °C (BRAZIL, 2009), so the increase in temperature predicted by the IPCC (2014) may affect the viability of the seeds.…”
Section: Introductionmentioning
confidence: 99%